Experimental Investigation of Ultrasonic Welding on Non-metallic Material. (2016) - Parmar, Umang; Pandya, D.H.
Abstract: In the present scenario of developing plastic utility in engineering applications, demand for reliable and faster joining processes has increased. Ultrasonic welding of thermoplastic is one of those joining methods which is based on application of high- frequency vibratory energy in that work pieces are held together under pressure without melting. Ultrasonic welding of thermoplastic composites has become an important process in industry because of its relatively low cost and high quality resultant joints This study involves modelling of experimental data of joint strength of acrylonitrile butadiene styrene (ABS) material for ultrasonic welding on welding parameters (welding pressure, welding time, amplitude). In order to determine critical states of the welding parameters, analysis of variances has applied while optimisation of the parameters affecting the joint strength has achieved with centre composite method of the Response Surface Methodology.